New traveling wave solutions of a nonlinear diffusion–convection equation by using standard tanh method - Seham I. Aziz; Wafaa M. Taha; Raad A. Hameed; Ibrahem M. Taha (Tikrit Journal of Pure Science)
Exact solutions of traveling wave are acquired by employ a relatively new technique which is called standard tanh method for a nonlinear diffusion–convection equation. The tanh method is applied for the first time for finding travelling wave solutions for the nonlinear diffusion–convection equation , where n and m, are integers, and , of order (m=4, n=7) and (m=5, n=9). Analytical solutions of a nonlinear diffusion–convection equations are obtained as a polynomial in tanh(x), and the plots for exact solutions are given. The obtained results are compared with F-Expansion method to validate the proposed approach.